(untitled) (Research, Society and Development, 2023)
Without parameters for carrying out a staff dimensioning, to maintain or expand the composition of a management team of integrative practices in public health, this is the first article to present the identification of the work processes of this type of team, with verification of execution and prioritization, the first step towards a future sizing of personnel. It used the methodology described by the Ministry of Health for administrative areas. The stages of identification and prioritization of processes were achieved, observation of the current effort per result, from the team’s point of view, and verification of the type of improvement solution for each process. 17 work processes were systematized, all identified with a high level of added value. For process improvement, the need to invest in people was the most frequent, followed by process optimization. The general result indicated great complexity associated with the work of the team, which has intersectoral actions and a wide range of activities in the network, at the three levels of health care. The intervention carried out, followed by recording and monitoring of activities and results over time, can help current and future workforce management for integrative practice management teams.